2019
DOI: 10.3390/ijms20081949
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-13 and IL-13Rα2 Expression by IL-32θ in Human Monocytic Cells Requires PKCδ and STAT3 Association

Abstract: Interleukin (IL)-32θ, a newly identified IL-32 isoform, has been reported to exert pro-inflammatory effects through the association with protein kinase C delta (PKCδ). In this study, we further examined the effects of IL-32θ on IL-13 and IL-13Rα2 expression and the related mechanism in THP-1 cells. Upon stimulating IL-32θ-expressing and non-expressing cells with phorbol 12-myristate 13-acetate (PMA), the previous microarray analysis showed that IL-13Rα2 and IL-13 mRNA expression were significantly decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Several studies from Yoon and coworkers have shown intracellular interactions of IL-32, protein kinase C (PKC), and signal transducer and activator of transcription 3 (STAT3) 57,70,[107][108][109][110] (Fig. 2).…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…Several studies from Yoon and coworkers have shown intracellular interactions of IL-32, protein kinase C (PKC), and signal transducer and activator of transcription 3 (STAT3) 57,70,[107][108][109][110] (Fig. 2).…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…It forms a stable dimer to translocate into the nucleus of stimulated cells and acts as a transcription factor for numerous targeted genes. Activation of STAT3 is induced by various cytokines (interleukin (IL)-6, type I interferons) and growth factors (epidermal growth factor (EGF), platelet-derived growth factor (PDGF)) through receptors (EGFR, PDGFR) and Janus kinase (JAK) signaling pathway [ 33 , 34 , 35 , 36 , 37 , 38 ], or through oncogenic proteins (Ras, protein kinase C (PKC)) [ 39 , 40 , 41 ]. It is stringently controlled by several negative regulators, including phosphatases (Src homology region 2 (SHP2), phosphatase and tensin homolog (PTEN), CD45) [ 42 , 43 , 44 ], suppressor of cytokine signaling proteins (SOCS), mainly SOCS3 [ 45 ], and protein inhibitors of activated STAT (PIAS) proteins, particularly PIAS3 [ 46 ].…”
Section: Role Of Stat3 Signaling In Cancermentioning
confidence: 99%
“…The activation of STAT6 is the primary signaling event in the response to IL-4 or IL-13 (Cao et al, 2016). In certain experimental conditions STAT1 and STAT3 can also be activated by both IL-4 and IL-13 (Wang et al, 2004; Bhattacharjee et al, 2013; Pham et al, 2019). The cytoplasmic domain of human IL-13Rα1 contains two tyrosine residues, which might serve as docking sites for STAT3 (Hershey, 2003).…”
Section: Introductionmentioning
confidence: 99%